Synthesis and Pharmacological Activities of 2,3,4,10-Tetrahydro-3,10-dioxo-2-(substituted phenyl)-[1,2,4]triazino[4,3-a]indoles - Murugesh, K.; Saravanan, V.S.; Thomas Leonard, J.; Sonia, G. (Asian Journal of Chemistry, 2016)
In this study, for developing potent analgesic and antiinflammatory compounds, some new 3-substituted 1,2,4-triazino-indole derivatives have been synthesized and performed preliminary screening their in vivo analgesic and antiinflammatory activities at a single dose of 100 mg/kg in mice by acetic acid induced writhing test and a carrageenan induced hind paw edema model, respectively. Compounds 4b, 4d and 4g exhibited good analgesic activity and compounds 4a and 4g showed very good antiinflammatory activity.